PIC multi-user receiver for multi-rate combined CDMD and SDMA systems - Khatun, Sabira; Mohd Ali, Borhanuddin; Ismail, Alyani; Odeh, Idhal A. S. (2009)
The present invention generally relates to wireless mobile communication and in particular to combined CDMA and SDMA (C-SDMA) system as a multiple access technique. More particularly, the present invention relates to a method to mitigate the interference accrued due to cross-correlations in terms of spreading codes and spatial correlations in terms of Angle of Arrival (AoA). Interference mitigation is performed using Parallel Interference Cancellation (PIC) by which the invented receiver estimated the interference from interference user and then cancel this interference from the desired user in parallel scenario. This interference mitigation is able to maximize the channel capacity (maximize the number of users) by means of reducing the Bit Error Rate (BER) and system capacity. This is done with minimum number of codes, less delay and less complexity compared to other existing techniques.